A dual-emission Ba6Ca3Al2Si6O24: Eu2+, Mn2+ phosphor with energy transfer for plant-protecting LED lamps and ratiometric temperature. (1st August 2022) - Wang, Bingkun; Shi, Qiufeng; Guo, Haijie; Cui, Cai'e; Huang, Ping; Wang, Lei
Graphical abstract: A series of pure-phase phosphors, BCASO: Eu 2+ and BCASO: Eu 2+, Mn 2+, were successfully synthesized using a solid-state reaction method. Novel dual-emission BCASO: Eu 2+, Mn 2+ phosphors exhibit a broad emission spectrum including blue-green and red bands, which facilitates the absorption of Chlorophyll a/b and Phytochrome PR while avoiding excessive blue light damage to plants and energy wastage. On the basis that Eu 2+ and Mn 2+ ions have different thermal responses, the temperature sensitivity was further analyzed and it was found that the maximum Sa and Sr values were 0.171 and 0.333 % K −1, respectively. Abstract: A series of dual-emitting Eu 2+ -Mn 2+ co-doped Ba6 Ca3 Al2 Si6 O24 (BCASO) phosphors were prepared by a solid phase method at high temperature. The phosphors show a blue-green emission peaking at 500 nm and a red emission peaking at 600 nm under a single UV excitation, which facilitates the absorption of Chlorophyll a /b and Phytochrome PR, while avoiding excessive blue light damage to plants and energy wastage. The reason for the simultaneous appearance of blue-green and red light is the energy transfer from Eu 2+ to Mn 2+ . The corresponding process has been investigated by analyzing the spectrum and the decay lifetime variations. In addition, we have explored the thermal stability of the phosphors, which is also an important parameter especially in plant lighting. We have unexpectedly found that Eu 2+ and Mn 2+ ions have different thermal reactions during the stability study, which has opened up the possibility for temperature detection. Therefore, we have discussed temperature measurement characteristics, such as the relationship between FIR and T, absolute sensitivity (Sa ) and relative sensitivity (Sr ). The results confirmed that the BCASO: Eu 2+, Mn 2+ phosphor might have great applicational potential in plant-protecting and optical temperature measurement.